Growth and yield of onion (Allium cepa L.) as influenced by application of organic and inorganic fertilizers - Andishmand, Abdul Bari; Noori, Mohammad Safar (Journal of Scientific Agriculture, 2012)
This study was carried out to ascertain the effects of organic manure (farmyard manure, poultry manure, and vermicompost) and chemical fertilizers NPK (nitrogen, phosphorus, and potassium) on the growth and yield of onion. The research was consisting ten treatments with three replications. Different levels of nitrogen (0, 100, and 150 kg ha-1), phosphorus (0, 75, and 100 kg ha-1), potassium (0, 80, and 100 kg ha-1) fertilizers, and various rates of organic manures (20 ton ha-1 of farmyard manure, 20 t ha-1 of poultry manure and 15 t ha-1 of vermicompost) were applied to the soil at different combinations. The results of this study have shown that both inorganic fertilizers and organic manures significantly influenced all growth and yield parameters. Whereas, maximum plant height (50.50 cm) and bulb yield (30.75 t ha-1) were obtained at the combination of 20 t ha-1 farmyard manure + 150 kg ha-1 N + 100 kg ha-1 P2O5 + 100 kg ha-1 K2O. However, the minimum bulb yield (15.80 t ha-1) was observed with control where no fertilizer was applied. Therefore, application of 20 t ha-1 farmyard manure during field preparation followed by application of 150 kg ha-1 N + 100 kg ha-1 P2O5 + 100 kg ha-1 K2O can be recommended for optimal growth and maximum bulb yield of onion.